The Effect of Lavender Aromatherapy on College Students’ Attention - Giovana, Sharel; Anjani, Nadira Kurniawan Mulia; Putri, Nadhira Aulia; Qintari, Lathifanya Amanda; Apriliani, Sela; Farisandy, Ellyana Dwi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Adequate and relaxed learning conditions will create an individual focus and concentration so as to create an effective learning or work process. One condition of optimizing individual cognitive processes as an effort to increase focus and attention is to involve aromatherapy as a scent that can help build a relaxing learning atmosphere. Lavender aromatherapy itself is known to provide anxiolytic effects as an anti-anxiety which can provide a calming effect and increase a person's cognitive performance. Therefore, this study aims to see if there are any differences between the experimental group that was exposed to lavender aromatherapy and the control group that was not exposed to aromatherapy before working on The d2 of Attention Test measuring instrument. This study used the true experimental research strategy method, with a randomized two-group post-test-only design. In addition, a non-probability sampling method (convenience sampling) was used to obtain easily accessible participant data. Participants were psychology students who do not have any olfactory issues. The testing was carried out using Independent Sample T-Test analysis technique for different tests. The experimental results revealed that there was a significant difference between the experimental group and the control group with a significant difference in the average score. This proves that lavender aromatherapy has an influence on an individual attentional function. Kondisi belajar yang baik dan nyaman akan membuat seseorang fokus dan berkonsentrasi sehingga terciptanya proses belajar ataupun bekerja yang efektif. Salah satu bentuk dari mengoptimalkan proses kognitif seseorang sebagai usaha untuk meningkatkan fokus dan atensi adalah dengan melibatkan aromaterapi sebagai aroma yang dapat membantu membangun suasana belajar yang nyaman. Aromaterapi lavender sendiri dikenal dapat memberikan efek ansiolitik sebagai anti cemas yang dapat memberikan efek tenang dan meningkatkan gairah kinerja kognitif seseorang. Penelitian ini bertujuan untuk melihat perbedaan pada kelompok eksperimen yang diberikan paparan aromaterapi lavender dan kelompok kontrol yang tidak diberikan paparan aromaterapi sebelum mengerjakan alat ukur The d2 of Attention Test. Penelitian ini menggunakan metode true experimental research strategy, dengan randomized two group design posttest-only. Selain itu, digunakan metode non-probability sampling (convience sampling) untuk mendapatkan data partisipan yang mudah dijangkau. Partisipan merupakan mahasiswa psikologi yang tidak memiliki masalah penciuman. Pengujian dilakukan dengan menggunakan teknik analisis Independent Sample T-Test untuk uji beda. Hasil eksperimen menunjukkan terdapat perbedaan yang signifikan antara kelompok eksperimen dan kelompok kontrol dengan perbedaan skor rata-rata yang signifikan. Hal ini membuktikan bahwa aromaterapi lavender memiliki pengaruh terhadap fungsi atensi seseorang.